Narodziny narodowych patriotyzmów w amerykańskich prowincjach imperium hiszpańskiego - Rydz, Romuald (Biuletyn Historii Wychowania, 2023)
The Napoleonic invasion of the Iberian Peninsula in 1808 sparked off a crisis in the Spanish Empire in the Americas, culminating in its disintegration after two decades of struggle. As a result, several new Latin American states emerged on the ruins of the three–century–long Spanish rule in the Western Hemisphere. According to Benedict Anderson, the outbreak of independence revolutions had been preceded by the rise of fully formed nationalism, which became a significant political and cultural phenomenon in the Spanish provinces of the New World in the late 18th and early 19th centuries. However, Anderson’s ideas, presented in his work „Imagined Communities”, faced criticism from many historians who view the emergence and evolution of national identities in America as a result of a long process initiated by the conquest. In my article, I attempt to describe the stages of shaping national patriotisms in the American provinces of the Spanish Empire and identify the key elements influencing their development. Similar to the aforementioned researchers of Latin American history, I try to demonstrate that fully formed national patriotism had not arisen in the region until the collapse of Spanish rule in the New World. In my opinion, earlier forms had preceded it, such as Creole patriotism, American identification, and provincial identities. It was not until the outbreak of the independence revolutions when many of the leaders attempted to give the struggles a national character. In their endeavors, patriotic slogans were meant to become tools of support for revolutionary governments and fostering unity in all the social strata.